Mathematical modelling predicts synergistic anti-tumor effects of combining a macrophage-based, hypoxia-targeted, gene therapy with chemotherapy - Owen, Markus R (2011)
Tumor hypoxia is associated with low rates of cell proliferation and poor drug delivery, limiting the efficacy of many conventional therapies such as chemotherapy. Since many macrophages accumulate in hypoxic regions of tumors, one way to target tumor cells in these regions could be to use genetically engineered macrophages that express therapeutic genes when exposed to hypoxia. We describe here our use of a new mathematical model to simulate and compare the effects of conventional cyclophosphamide therapy with those induced when macrophages are used to deliver hypoxia-inducible cytochrome P450 to locally activate cyclophosphamide. Our mathematical model describes the spatio-temporal dynamics of vascular tumor growth and treats cells as distinct entities, each with its own cell cycle and subcellular signalling machinery. Moreover, the model simulates the delivery of systemically-applied therapies by a dynamic vascular network. We used this model to determine both the impact on tumors of combining conventional chemotherapy with macrophage-based gene delivery, and how the efficacy of macrophage-based therapies may be enhanced by pre-loading the cells with magnetic nanoparticles and applying a magnetic field to the tumor site. MAJOR FINDINGS: Our results predict that combining conventional and macrophage-based therapies would be synergistic, producing greater anti-tumor effects than the additive effects of each form of therapy. Moreover, we found that timing is crucial in this combined approach with efficacy being greatest when the macrophage-based therapy is administered shortly before or concurrent with chemotherapy. Lastly, we show not only that macrophage delivery of therapeutic genes is markedly enhanced using the magnetic approach described above, but also that the disorganised nature of tumor blood vessels means that this enhancement depends mainly on the strength of the applied field, rather than its direction. This may be important in the treatment of non-superficial tumors where generating a specific orientation of a magnetic field may prove difficult. In conclusion, we demonstrate that mathematical modelling can be used to design, and maximize the efficacy of, combined therapeutic approaches in cancer.